(untitled) (Colombia Medica, 2018)
Introduction: Most maternal deaths that occur in developing countries are considered unfair and can be avoided. In 2008, The World Health Organization (WHO) proposed a checklist for childbirth care, in order to assess whether a simple, low-cost intervention had an impact on maternal and neonatal mortality in low-income countries. Objective: To translate, adapt and validate the content of the WHO Safe Childbirth Checklist (SCC) for its use in Colombia Methods: The checklist was translated and adapted to the Colombian context. It was subsequently validated by a panel of experts composed of 17 health workers with experience in maternal and neonatal care and safety. Reliability among judges was estimated (Rwg) and items were modified or added to each section of the list according to the results. Results: Modifications were made to 28 items, while 19 new items were added, and none was removed. The most important modifications were made to the management guidelines included in each item, and the items added refer to risks inherent to our environment. Conclusion: The Colombian version of the SCC will be a useful tool to improve maternal and neonatal care and thereby contribute to reducing maternal and neonatal morbidity and mortality in our country.